The Theoretical Concepts of Innovative Potential Formation of National Economy - Kendiukhov, O.; Solokha, D.; Tanchyk, O. (Економічний вісник Донбасу, 2020)
The main approaches to optimizing the competitive advantages of economic entities of Ukraine in the context of the implementation of the main provisions of the concept of sustainable development, taking into account the criterion of environmental efficiency, are considered.
Producers of environmental innovations should take into account the impact of environmental pressures and negative environmental impacts when assessing their chances of market success. There are radical environmental innovations that have no direct analogues. For this type of innovation in the analysis of demand and assessment of market prospects are advised to consider the following factors: a critical consumer of capital, critical suitability of the product, the critical minimum level of income, the critical level of risk, and the critical amount of free time consumer. The speed of overcoming these barriers affects the time required to introduce environmental innovations to the market, start generating demand, and increase sales.
For the formation of the domestic market of environmentally friendly products, it is necessary to create an adapted regulatory framework to stimulate producers and create a competitive environment. The mechanism for developing a strategy for the development of economic entities for the production of environmentally friendly goods is presented. The strategy is presented as a generalizing model of the actions necessary to achieve the goal. It is advisable to carry out strategic actions according to a certain algorithm, which is a logical sequence.
The procedure for certification of environmentally friendly products and the algorithm of this process based on the criterion of environmental efficiency of production systems are proposed. Certification allows you to get complete and reliable information about the production of environmentally friendly goods at all stages, gives consumers a guarantee of compliance with the norms and standards that confirm the environmental purity of products.
Objective comprehensive identification of the needs of the main consumer groups gradually forms the basis for the functioning of the market of environmentally friendly products. The diagnostic approach to its formation should be used in combination with the optimization approach, which is implemented through the formation and implementation of an appropriate strategy, the development of the legislative framework, the structure and infrastructure of the market. Розглянуто основні підходи до оптимізації конкурентних переваг господарюючих суб’єктів України в контексті реалізації основних положень концепції сталого розвитку з урахуванням критерію екологічної ефективності.
Виробникам екологічних інновацій при оцінці своїх шансів на ринковий успіх слід враховувати вплив факторів екологічного тиску і негативного впливу навколишнього середовища. Існують радикальні екологічні інновації, які не мають прямих аналогів. Для даного виду інновацій при аналізі попиту та оцінці ринкових перспектив рекомендується враховувати наступні фактори: критичний рівень споживчого капіталу, критичну придатність продукту, критичний мінімальний рівень доходу, критичний рівень ризику і критичний обсяг вільного часу споживача. Швидкість подолання цих бар’єрів впливає на час, необхідний для впровадження екологічних інновацій на ринок, початок генерування попиту і збільшення продажів.
Для формування внутрішнього ринку екологічно чистої продукції необхідно створити адаптовану нормативну базу для стимулювання виробників і створення конкурентного середовища. Представлено механізм розробки стратегії розвитку господарюючих суб’єктів з виробництва екологічно чистих товарів. Стратегія представлена як узагальнююча модель дій, необхідних для досягнення мети. Стратегічні впливи доцільно здійснювати за певним алгоритмом, що представляє собою логічну послідовність.
Запропоновано процедуру сертифікації екологічно чистих товарів та алгоритм даного процесу на основі критерію екологічної ефективності виробничих систем. Сертифікація дозволяє отримати повну і достовірну інформацію про виробництво екологічно чистого товару на всіх етапах, дає споживачам гарантію дотримання норм і стандартів, що підтверджують екологічну чистоту продукції.
Об’єктивне комплексне виявлення потреб основних груп споживачів поступово формує основу функціонування ринку екологічно чистих товарів. Діагностичний підхід до його формування повинен використовуватися в поєднанні з оптимізаційним підходом, який реалізується шляхом формування та реалізації відповідної стратегії, розробки законодавчої бази, структури та інфраструктури ринку. Рассмотрены основные подходы к оптимизации конкурентных преимуществ хозяйствующих субъектов Украины в контексте реализации основных положений концепции устойчивого развития с учетом критерия экологической эффективности.
Производителям экологических инноваций при оценке своих шансов на рыночный успех следует учитывать влияние факторов экологического давления и негативного воздействия окружающей среды. Существуют радикальные экологические инновации, не имеющие прямых аналогов. Для данного вида инноваций при анализе спроса и оценке рыночных перспектив рекомендуется учитывать следующие факторы: критический уровень потребительского капитала, критическую пригодность продукта, критический минимальный уровень дохода, критический уровень риска и критический объем свободного времени потребителя. Скорость преодоления этих барьеров влияет на время, необходимое для внедрения экологических инноваций на рынок, начало генерирования спроса и увеличение продаж.
Для формирования внутреннего рынка экологически чистой продукции необходимо создать адаптированную нормативную базу для стимулирования производителей и создания конкурентной среды. Представлен механизм разработки стратегии развития хозяйствующих субъектов по производству экологически чистых товаров. Стратегия представлена как обобщающая модель действий, необходимых для достижения цели. Стратегические воздействия целесообразно осуществлять по определенному алгоритму, представляющему собой логическую последовательность.
Предложена процедура сертификации экологически чистых товаров и алгоритм данного процесса на основе критерия экологической эффективности производственных систем. Сертификация позволяет получить полную и достоверную информацию о производстве экологически чистого товара на всех этапах, дает потребителям гарантию соблюдения норм и стандартов, подтверждающих экологическую чистоту продукции.
Объективное комплексное выявление потребностей основных групп потребителей постепенно формирует основу функционирования рынка экологически чистых товаров. Диагностический подход к его формированию должен использоваться в сочетании с оптимизационным подходом, который реализуется путем формирования и реализации соответствующей стратегии, разработки законодательной базы, структуры и инфраструктуры рынка.